A sustainable C–H functionalization of indoles, pyrroles and furans under a blue LED with iodonium ylides. Issue 35 (24th August 2021) - Sar, Saibal; Das, Ranajit; Barman, Dhiraj; Latua, Pikaso; Guha, Souvik; Gremaud, Ludovic; Sen, Subhabrata
Abstract : Pyrrole and indole derivatives are functionalized with the dimethyl malonate derived phenyl iodonium ylide in the presence of a blue LED via C–H functionalization of the respective heterocycles in methanol to generate the desired compounds. Abstract : Pyrrole and indole derivatives are functionalized via a green initiative with the dimethyl malonate derived phenyl iodonium ylide 4a in the presence of a blue LED via C–H functionalization of the respective heterocycles in methanol to generate the desired compounds 5–7 in moderate to good yields. Control experiments provide insight into the probable reaction mechanism. Finally, the strategy is successfully applied in the generation of azepino[4, 5- b ]indole 12a /b .